2023
DOI: 10.1002/hsr2.1394
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of factors influencing ePHR adoption by caregivers and care providers of Alzheimer's patients: An extension of the unified theory of acceptance and use of technology model

Abstract: Background and Aims: As the nowadays provision of many healthcare services relies on technology, a better understanding of the factors contributing to the acceptance and use of technology in health care is essential. For Alzheimer's patients, an electronic personal health record (ePHR) is one such technology. Stakeholders should understand the factors affecting the adoption of this technology for its smooth implementation, adoption, and sustainable use. So far, these factors have not fully been understood for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…However, parallel findings suggest that unpaid carers commonly experience split feelings towards ICT. Amiri et al (2023) , Hwang et al (2020) and Dai et al (2019) recorded how carers perceived digital health services and wearable devices to be useful for communicating with care practitioners and accessing timely information and support. Similarly to current participants, the studies also reported that carers with lower digital self-efficacy felt impeded by the presentation and language of the ICT systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, parallel findings suggest that unpaid carers commonly experience split feelings towards ICT. Amiri et al (2023) , Hwang et al (2020) and Dai et al (2019) recorded how carers perceived digital health services and wearable devices to be useful for communicating with care practitioners and accessing timely information and support. Similarly to current participants, the studies also reported that carers with lower digital self-efficacy felt impeded by the presentation and language of the ICT systems.…”
Section: Discussionmentioning
confidence: 99%
“…Parastoo Amiri et al conducted a qualitative study on factors influencing ePHR adoption by caregivers and care providers of Alzheimer's patients, extending the UTAUT model. Their research emphasizes the role of perceived security and privacy in healthcare technology adoption, aligning with UTAUT constructs [32]. The Unified Theory of Acceptance and Use of Technology (UTAUT) serves as a comprehensive framework for understanding user perceptions, intentions, and behaviours in the context of technology adoption, with a particular focus on security and privacy considerations.…”
Section: Privacy and Security: Unified Theory Of Acceptance And Use O...mentioning
confidence: 99%